THE METHODOLOGY OF TEACHING ENGLISH IN SCHOOL - Quvondiqova, Madina (Журнал иностранных языков и лингвистики, 2021)
Abstract The aim of this practice was to discover the most effective ways of teaching a foreign language to children. In formation of interest to a subject the huge role is played by the person of the teacher. Therefore a vow of effective dominating English language by the understudies is demonstrable skill of the educator which ought to in the work not just consider the deliberate standards hidden instructing, yet additionally to be in steady inquiry of new gatherings and method for showing which will recuperate something new, will make it intriguing, intellectual and recollected. Keywords: methods, teacher', didactic principles, vocabulary, grammar, pedagogical process, pupils, aspects of language, integration, speech units.